Strengthening Culture Through Historical Elements, Origins of Village Naming and Folk Games in Lalingato Village, Tirawuta District, East Kolaka Regency - Laxmi; Fina Amalia; Aswati; Erens Koodoh; Suriana (Peneliti Teknologi Teknik Indonesia, 2023)
The community service activities carried out in Lalingato Village, Tirawuta District, East Kolaka Regency were carried out collaboratively with the 2022 UHO Regular KKN student program. These community service activities can be carried out in accordance with the expectations of the community. Based on the results of the implementation, this activity received a good response from the principal and teachers of SDN 1 Lalingato so that this activity could run smoothly according to the expectations of the service team, namely to be able to provide knowledge to the community, especially students at SDN 1 Lalingato about History, Origins Village Names and Folk Games in Lalingato Village, Tirawuta District, East Kolaka Regency.